2019
DOI: 10.3390/su11030835
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Diets and Reduced Land Pressure: Towards a Double Gain for Future Food Systems in Nigeria

Abstract: Nigeria is one of the most dynamic economies in Africa. Strong GDP and population growth coupled with urbanization trends place tremendous pressures on natural resources and the food systems that are dependent on them. Understanding the impact of these “mega trends” is important to identify key leverage points for navigating towards improved nutrition and food security in Nigeria. This paper contributes to the Foresight Project of the Food Systems for Healthier Diets which aims to analyse how the food system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The general agreement in the literature has been that a traditional Nigerian diet was high in carbohydrates and fibre, low-to-moderate in fats, and relatively low in protein [1,2,[5][6][7][14][15][16][17][18][19]. The 2018 LSMS survey [12], which enquired from more than 5000 households across the country what foods they had consumed in the preceding week, suggested that Nigerian reliance on carbohydrates for calories has continued, even though it is slightly below the sub-Saharan African average of 71%, at about 69% of daily energy intake per capita [20].…”
Section: Typical Nigerian Dietmentioning
confidence: 98%
See 1 more Smart Citation
“…The general agreement in the literature has been that a traditional Nigerian diet was high in carbohydrates and fibre, low-to-moderate in fats, and relatively low in protein [1,2,[5][6][7][14][15][16][17][18][19]. The 2018 LSMS survey [12], which enquired from more than 5000 households across the country what foods they had consumed in the preceding week, suggested that Nigerian reliance on carbohydrates for calories has continued, even though it is slightly below the sub-Saharan African average of 71%, at about 69% of daily energy intake per capita [20].…”
Section: Typical Nigerian Dietmentioning
confidence: 98%
“…Urban families in the dataset consumed almost all the food groups assessed more frequently, except for sweets and alcohol (Table 3). Urban consumption exceeded rural consumption particularly in animal-sourced foods (see also [18]) and vitamin A-rich fruits and vegetables. A more detailed look at the data reveals that the consumption of traditional or indigenous foods was higher in rural than in urban areas (Table A5).…”
Section: Differences By Areamentioning
confidence: 99%
“…A further diversification of the food supply will have to coincide with a higher productivity of staple crops, in particular rice and maize (Smeets-Kristkova , Acterbosch , & Kuiper, 2019). In recent decades, agricultural output growth was mainly based on an expansion of the area under cultivation, adding to conflict over scarce grazing land and water -often at the expense of pastoral livestock farming.…”
Section: Biophysical Driversmentioning
confidence: 99%
“…Economy-wide methods such as computable general equilibrium (CGE) models are well suited to assess the long-term impact of fiscal policies, because they capture all economic linkages and interactions between all sectors and institutions within the domestic economy and foreign trade (Ecker et al, 2012). These models have been used in the past to do foresight studies focused on food security (Brinkman et al, 2020;Doelman et al, 2019;van Meijl et al, 2020) and to assess the possibilities to transform country-level food systems to promote healthy diets (Kuiper and Cui, 2020;Latka et al, 2021;Smeets-Kristkova et al, 2019). Likewise, coupling CGE models with microsimulations is an approach that has been employed to assess food and nutrition outcomes (Breisinger and Ecker, 2014).…”
Section: Introductionmentioning
confidence: 99%